Fintech and financial inclusion: the case of Banco Maré - Giarelli, Stefano (2018)
The city of Rio de Janeiro has the highest proportion of people living in slums in all Brazil, with more than 22% of its inhabitants living in those places . These people suffer from the lack of or limitation in the provision of basic services such as sanitation, health, education and safety. The case for financial services is no different. Although living in urban centers, inhabitants of slums have very restricted access to financial services, often needing to commute to other neighborhoods to make a simple payment, adding more costs, risks and loss of time to their lives. This research uses an exploratory case study method to examine a fintech called Banco Maré, created to improve financial inclusion in the largest complex of slums of Rio de Janeiro, the Complexo da Maré. The study draws on Sen’s capability approach - which considers development as much more than income growth in a holistic understanding of human development - and information and communication technology for development (ICT4D) literatures to address the problem of development in these communities. A model for financial inclusion, adapted from Joia & Dos Santos (2017) and based on the aforementioned literatures is used to evaluate the initiative. Two units of analysis are used in the research design to compare different locations and generate further insights into the process of generating financial inclusion in the region. Content and lexical analyses are used to examine data gathered from interviews. The analyses are corroborated by other sources of evidence such as documentation research, visual records and direct observation. The results suggest that Banco Maré has generated limited financial inclusion in the region, though it shows a significant potential to broadening access and use of financial services. Furthermore, it indicates that slight improvements in the institutional order of the locations, may greatly impact the results of financial inclusion initiatives.